THE EFFECT OF INNOVATION AND ENTREPRENEURIAL INTENTION TO FIRM PERFORMANCE - Suresh Kumar; Mei Andriani (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The purpose of this research is to measure the effect of entrepreneurial orientation and the types of innovation (product, process, marketing) to the firm performance. Little attention, however, has been given to the possible impact of various dimensions of innovation on firm performance. To achieve this purpose, the authors evaluate the impact of entrepreneurial orientation and the types of innovation on the performance of small and medium enterprises (SMEs). This study applied a quantitative design. The questionnaires were distributed manually and digitally to 236 workers who work in the smalland medium enterprises (SME) in Jababeka,Cikarangarea–Indonesia. The data were analyzed using a hierarchical regression analysis. The findings confirmed the hypothesis that entrepreneurial orientation and type of innovation influenced firm performance significantly.Keywords: Innovation, entrepreneurial orientation, firm performance, SMEs, Indonesia.